About the modeling of light beam self-focusing in plasma at the irradiation of the target by power UV laser - I. G. Lebo (Российский технологический журнал, 2021)
The peculiarities of light beam expansion in plasma upon irradiation of condensed targets with a powerful UV laser pulse are studied with the help of mathematical modeling. Experiments were carried out at the Lebedev Physical Institute of the Russian Academy of Sciences with the use of GARPUN installation: a powerful KrF laser that irradiated two-layer targets consisting of aluminum foil and a plexiglass layer. Channels stretched along the direction of incidence of the laser beam were found at the bottom of the crater. It was shown on the basis of experimental and calculated data that selffocusing of the laser beam developed in the plasma. As a result, hot spots were produced in vicinity of the plasma critical density, and fast (superthermal) electron flows were generated. The electron flows could produce the channels in the plexiglas. In order to describe the self-focusing effect a physicalmathematical model was developed, and “FOCUS” program was created at the Russian Technological University (MIREA). Numerical simulations were carried out on the gas-dynamic profiles (linear and exponential). It was shown that thermal self-focusing could develop at the conditions of “GARPUN” experiments (~ 1 mm longitudinal plasma, moderate radiation intensity: 1011–1012(W/cm2) × µm2).  The parameters of dangerous modes of laser beam perturbations were estimated. The interest in the experimental and mathematical modelling results is related to the laser thermonuclear fusion (LTF) research. Although Nd glass lasers are the basic installations for LTF research, UV gas eximer lasers have some advantages as drivers for future thermonuclear fusion reactors. The interaction of UV laser radiation with plasma has some peculiarities. Thus, developing physical-mathematical models and creating new programs required for the interpretation of modern UV laser – plasma coupling experiments and for the design of large scale facilities based on eximer drivers is a topical problem.